Trust to Judiciary in Turkey and Factors Affecting Trust in The Judical - Örselli, Erhan; Bilici, Zekeriya (The journal of contemporary issues in business and government, 2021)
Modern states realize their legitimacy and the monopoly of legitimate use of force through the judiciary. Citizens' trust in the state is directly related to their trust in the judiciary. In countries that have adopted the rule of law and democracy, the citizens' lack of trust in the judiciary causes many problems. In this context, in modern and democratic countries, it is of great importance to understand the trust of the citizens in the judiciary and the factors that affect this, and to determine the level of belief that justice is impartially, independently and quickly established. The results of the study on the trust of citizens in the judiciary at various times in Turkey show that the decrease of trust in the judiciary and shows that it is at very low levels. The aim of this study was to determine the level of trust in the judiciary in Turkey. In the study, it is tried to measure the trust of the citizens in the judiciary and their perceptions and attitudes on this issue. In this context, “What is the trust level of citizens in the judiciary? What factors affect citizens' trust in the judiciary?” answers to such questions are sought. The study aims to determining the trust of citizens in the judiciary and Turkey in line with a survey was carried out in order to determine the factors affecting it.